The Relationship Between Knowledge and Attitudes With The Incidence of Stunting In Pre-School Children In The Sub-District of Kota Lama Kupang City - Jenireinildis Letek Doni; Astuti Nur (Jurnal Gizi dan Kesehatan Keluarga, 2023)
Early childhood is a golden age for child development to obtain the educational process. Early childhood education in the form of providing stimulation by parents, teachers and the immediate environment is needed to optimize the ability and development of children to grow and develop according to their phase. This study aims to determine the relationship between knowledge and attitudes with the incidence of stunting in PAUD children in Kota Lama District, Kupang City. The type of research used is cross sectional research. Sampling in this study was done by total sampling method. The number of samples was 45 toddlers. The number of stunted toddlers in Kota Lama District amounted to 15 toddlers (46.7%), not stunted as many as 30 toddlers (53.3%) out of a total of 45 toddlers. The level of knowledge of mothers of toddlers with a good category was 7 people (15.6%), a moderate category of 15 people (33.3), and a category of less than 23 people (51.1). Maternal attitudes with positive categories were 17 people (37.8%), and negative categories were 28 people (62.2%). There is no relationship between maternal knowledge and the incidence of stunting in PUAD children in Kota Lama District with a p value of : 0,126> (0,05). There is no relationship between maternal attitudes and the incidence of stunting in PUAD children in Kota Lama District with a p value: 0.082> (0.05).